Evaluasi Penerapan Manajemen Waktu pada Proyek Pembangunan Gedung Workshop Pembelajaran Ketrampilan SMKN 1 Magetan (Eduscotech, 2023)
In building construction, it is not uncommon for service users to place many demands on construction service providers, one of which is that the work must be completed on time. Therefore, time management is needed that is able to sharpen priorities and is also able to increase the efficiency and effectiveness of project management in order to achieve maximum results with the available resources. The aim of this research is to determine the application of time management carried out in the Vocational School 1 Magetan Skills Learning Workshop Building Construction projectThis research requires two types of data, namely primary data taken from interviews and field observations; and secondary data sourced from construction service providers, in the form of weekly progress reports and time schedules. Network analysis was carried out using the Critical Path Method (CPM).The implementation of time management has been carried out well, as can be seen from the large deviations that occurred, one of which was in the sixth week, namely 20.57%. Obstacles faced in carrying out project time management include delays in work due to limited availability of materials in the field, waiting for confirmation from the owner due to changes in work specifications, and lack of coordination between ceiling craftsmen and electrical installers which causes delays in painting work. The solutions implemented for the obstacles encountered were increasing the availability of materials, holding meetings with the owner and other related agencies, coordinating with the workforce to prevent missed communications. The alternative is to carry out work in parallel, implement an overtime work system, and increase the number of workers in the field. Network analysis using the CPM method produces a critical path for 13 types of work with a completion time of 22 weeks.